Building log book for small businesses. (CIBSE, 2006)
Part L 2006 requires that building owners be provided with summary information about a new or refurbished building, its building services and their maintenance requirements in a building log book. CIBSE TM31 explains what sort of information the log book should contain. The CIBSE Building log book tool kit templates offer a standard format for the summary. This covers how a building is intended to work and how it is meant to be maintained and serviced. They also provide a means to record the energy use and maintenance of the services within the building. Log books provide a simple, easily accessible summary of a new or refurbished building rather than the detail contained in O & M manuals. The easy way to show compliance with new Part L is to produce a building log book based on the template and guidance in CIBSE TM31. It gives detailed guidance on the scope, structure and contents of the log book, who should write it and who should keep it up to date. --